William Blake’s legacy in Miguel de Unamuno’s mature poetry and poetics - Flores Moreno, Cristina (Estudios Ingleses de la Universidad Complutense, 2011)
It is the main purpose of this article to dive into the nature and extent of William Blake’s contribution to Miguel de Unamuno’s late poetry and poetics. The initial study of Unamuno’s pencilled marks on his own volumes of Blake’s complete works, together with the analysis of the essays and poem he devoted to the British author are aimed at providing an accurate dating of Unamuno’s reading of Blake’s works, establishing thus the period of greatest influence, as well as casting some light as regards those aspects of Blake’s thought that most appealed him. Finally, the echoes of Blake’s concepts and images will be traced in Unamuno’s mature works.